2018
DOI: 10.1017/ice.2018.177
|View full text |Cite
|
Sign up to set email alerts
|

Emerging outbreaks associated with conflict and failing healthcare systems in the Middle East

Abstract: The escalating conflicts in the Middle East have been associated with the rapid collapse of the existing healthcare systems in affected countries. As millions of refugees flee their countries, they become vulnerable and exposed to communicable diseases that easily grow into epidemic crises. Here, we describe infectious disease epidemics that have been associated with conflicts in the Middle East, including cholera, poliomyelitis, measles, cutaneous leishmaniasis, and diphtheria, that call for appropriate preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 30 publications
(74 reference statements)
2
28
0
Order By: Relevance
“…Our findings support a recent study that suggested that measles outbreaks among migrants in the European Union were due in part to sub-optimal vaccination coverage [31]. Enhanced cross-border surveillance with targeted screening and treatment of infectious diseases have been demonstrated to improve the health outcomes of forcibly displaced persons before resettlement and is recommended to be pursued in outbreak settings as well [32][33][34][35].…”
Section: Fig 1 Flow Chart Of Search Strategysupporting
confidence: 87%
“…Our findings support a recent study that suggested that measles outbreaks among migrants in the European Union were due in part to sub-optimal vaccination coverage [31]. Enhanced cross-border surveillance with targeted screening and treatment of infectious diseases have been demonstrated to improve the health outcomes of forcibly displaced persons before resettlement and is recommended to be pursued in outbreak settings as well [32][33][34][35].…”
Section: Fig 1 Flow Chart Of Search Strategysupporting
confidence: 87%
“…This is much lower than the prevalence reported by similar health facility-based studies in Ethiopia such as Addis Ababa 14.2% [33]. Although the nationwide prevalence of CL is lacking in Ethiopia, there are some community-based cross-sectional surveys showing 2.3-14.0% prevalence [15,23,24,27] from various parts demonstrating remarkable heterogeneity. A meta-analysis and systemic review [37] reported a pooled prevalence of 19.0%.…”
Section: Discussionmentioning
confidence: 71%
“…At a global level, studies show that in a mediumsized country, conflict can increase malnutrition by 3.3%, reduce life expectancy by 1 year, increase infant mortality by up to 10%, and cause other public health problems due to lack of access to drinking water, food and health services [7]. Although the epidemiological profile and burden of disease of countries in conflict has changed in the last decades, infectious diseases like malaria, tuberculosis, leishmaniasis, cholera, acute diarrheal disease and poliomyelitis, continue to be serious problems [8][9][10]. Conflict can also have devastating effects on sexual and reproductive health, neonatal health, mental disorders and noncommunicable diseases, such as cancer, hypertension and diabetes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%